DYNAMIC OPTIMAL FUTURES HEDGING WITH JUMP RISK AND STOCHASTIC INTEREST RATES - Chahdoura, Nabil; Chau To, Minh; Laroche, Pierre (Assurances)

(untitled) (HEC Montréal, 2002)
In this paper, we derive dynamic optimal futures hedge ratios when the relative change in the spot price follows a Poisson jump-diffusion process, and when basis and marking-to-market create additional risks. We show that our hedge ratios could be more efficient than the regression hedge ratio, and those obtained by Chang, Chang and Fang (1996a, 1996b), either because of a different model specification, or because of a different process specification. We apply our model to the West Texas Intermediate crude oil contract quoted on the NYMEX, and we show that our hedge ratios are more efficient than the other ratios under the shorter hedging horizons.